Geospatial Assessments of Urban Green Space Protection in Abuja City, Nigeria - Enoguanbhor, Evidence Chinedu (Eximia, 2022)
In the Global South, including Sub-Saharan Africa, several reports have shown that urban planning strategies have failed to protect effectively the new and existing urban green infrastructures. However, while most of those studies did not limit their scales to the implemented urban planned areas, others did not conduct a direct comparison between the observed urban green space and those designated by urban plans. Using Abuja, Nigeria as a case study, urban plan, and Geographic Information Systems/remotely sensed data were combined to assess the urban green space protection within the implemented urban planned areas to support urban strategic actions such as urban policies, planning, and programs for urban environmental sustainability. Supervised classification of land cover was performed on a Sentinel 2 satellite image to assess the spatial patterns of urban green space for 2021. Also, the association between the observed urban green space and that of the urban plan was quantified and compared. Additionally, the level of urban green space protection within individual parks and gardens was investigated. Key findings indicated that while some parks/gardens are moderately protected, others are highly protected. Additionally, the findings showed positive and significant associations between the observed urban green space and land use designated for urban green space by the urban plan. This study showed the effectiveness of the implementation of urban strategic actions for the protection of urban green infrastructures within the implemented urban planned areas in Abuja, Nigeria, which may be the case for other cities in Sub-Saharan Africa and other parts of the world, where such urban strategic actions are being implemented. The findings provided in this study are crucial to support the decision-making process in urban strategic actions on the protection of urban green infrastructures and to improve urban environmental sustainability in Sub-Saharan Africa and other parts of the world.